DIGITALIZATION OF WORK IN THE MIRROR OF LABOUR LAW PRINCIPLES IN HUNGARY - Mélypataki, Gábor (PEOPLE: International Journal of Social Sciences, 2021)
The field of labor law can be characterized primarily as a legal branch regulating personal relations. Of course, this is true for most of the legal branches as well. But fewer legal regulatory fields can tell that there is a relation between the parties with a specific nature of trust. Of course, this is not classic trust, but it is similar. The relation between the employer and the employee usually supposes a relation based on long-term personal contribution in which all the participants have their task, right, and obligation. We are talking about a complex relationship system in which personal nature and stability have an especially important role. I want to illustrate the impact of digitalization on employment through the principles of labor law. To this end, I will focus on the general behavioral requirements of digitalization. I will also explore the meaning of the principles in this changed context. It will be necessary to regulate future forms of employment, but it will also be necessary to find the relevant legal basis. This article seeks to identify these legal bases.